Igbo Apprenticeship Practice: Resilience Vehicle for Venture Creation in Southeastern Nigeria - Friday, Ogbu Edeh; Blessing, Friday Edeh; Neji, Desmond Oben; Collins Irem, Okechukwu; Onah, Gladys Owere; Prince, Alamina Ule (INTI International University, 2025)
In the quest to generate wealth that could salvage the ravaging poverty after the Nigeria-Biafra Civil War, the Igbo-speaking people of southeastern Nigeria birthed apprenticeship practice which has until this day become a norm in the region. It was based on the relevance of this entrepreneurial spirit of the Igbo people and how they have consistently embraced apprenticeship culture to reduce unemployment and create new businesses across the Nigerian space that motivated the researchers to carry out this investigation with 204 mentors (Oga’s) that passed through the apprenticeship practice before establishing their businesses. The purpose of this investigation is to examine the relationship between Igbo apprenticeship practice and venture creation in Southeastern Nigeria. The theories that explained Igbo apprenticeship practice are social learning theory and Igwebuike theory. Descriptive statistics and regression were used to analysed the data. The study found that Igbo apprentice practice has a significant positive relationship with venture creation and job creation in the southeastern region of Nigeria